Analisis Beban Fisiologi Kerja pada Penggunaan Masker Wajah saat Melakukan Aktivitas Fisik - Shofa Aulia Aldhama; Chandrawati Putri Wulandari; Rike Surya Shafarani; Valencia Tesalonika; Priskila Yohana; Tozati Intan Ramadhani; Gilang Fadly Hassani (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2022)
During the COVID-19 pandemic people are required to limit outside activities and keep following social distancing protocol. However, several studies have reported that indoor exercises have a greater risk toward COVID-19 virus infection. Therefore, wearing a mask during light to moderate intensity of outdoor physical activity is still recommended. We conduct an experiment to analyze physiological ergonomics aspect, whether people wearing different type of masks during physical activities and distraction of music would affect heart rate. Analysis of the average heart rate data was carried out using the calculation of VO2max and Energy Expenditure to determine the workload level of the four scenarios of treatment combination. The result shows a heavy level of physical load on the use of surgical mask with distraction of music and moderate level of physical load on the use of surgical without distraction of music.